Relationship between Gentamicin Administration and Ductal Patency in Very Low Birth Weight Infants - Cakir, Ufuk; Tayman, Cuneyt (Current Reviews in Clinical and Experimental Pharmacology, 2022)
Background: Patent Ductus Arteriosus (PDA) is associated with adverse clinical outcomes in very low birth weight (<1500g) infants. Objective: In our study, it was aimed to investigate the effect of gentamicin treatment, which is frequently used for early-onset sepsis on ductal patency. Methods: We performed a single-center retrospective review of charts of preterm infants <32 weeks gestation with birth weight <1500 grams born between June 1, 2015 and December 31, 2019 at the neonatal intensive care unit. All infants underwent an echocardiogram (ECHO) at 72 hours. To determine the effect of gentamicin treatment on hemodynamically significant PDA (hsPDA), we compared the frequency and duration of gentamicin administration between infants with hsPDA and without hsPDA. Results: During the study period, 792 patients were evaluated. Gentamicin was given to more infants with hsPDA than to those without hsPDA (89.2% vs. 64.6%, p<0.001), and the duration of therapy was longer in those infants with hsPDA (7 days vs. 9 days, p<0.001). The area under the curve for duration of gentamicin was 0.772 (%95 CI: 0.742-0.804, P=0.0001), sensitivity: 59 (%95 CI: 53-65), specificity: 82 (%95 CI: 78-88), with a cut-off day for duration of gentamicin >7 days. Conclusion: In our study, it was found that ductal contraction decreased and hsPDA rate increased as the rate and duration of gentamicin increased.
Keywords: premature